Bis(1,10-phenanthroline-κ(2) N,N′)(sulfato-κ(2) O,O′)nickel(II) ethane-1,2-diol solvate - Zhong, Kai-Long (International Union of Crystallography, 2009)
In the title compound, [Ni(SO(4))(C(12)H(8)N(2))(2)]·C(2)H(6)O(2), the coordination polyhedron around the Ni(2+) ion is a distorted octahedron, with four N atoms from two phenanthroline groups and two O atoms from a bidentate sulfate ligand. The Ni(2+) ion lies on a special position of site symmetry 2. Intermolecular O—H⋯O hydrogen bonds help to stabilize the structure. The OH group of the ethane-1,2-diol solvent is disordered over two positions with equal occupancy.